La aplicación de los elementos constitutivos de la tipicidad objetiva en las sentencias condenatorias por femicidio. - Marcillo, Segundo V. (2022)
The purpose of this professional article is to analyze the application of the constitutive elements of objective typicity in two convictions for femicide, issued by the Court of Criminal Guarantees of Imbabura in the year 2021. The legal problem arises when the judges of the courts of criminal guarantees, when analyzing the constitutive elements of an objective type to dictate convictions or acquittals, find that they are not clearly defined in terms of the active subject, the passive subject, the conduct or governing verb, the legal object, the material object and the normative element; which gives as a result that in the convictions issued by the criminal courts there is no clarity or uniformity in their application. In the present investigation, the qualitative approach was used, the descriptive, explanatory and relational level. The type of research used is documentary, for which the documentary analysis technique was applied with its respective instrument, which is the documentary analysis sheet, and the method used is scientific. Determined the elements of objective typicity according to the doctrine and analyzing the two convictions issued in 2021, the result was that they do state some of their elements, without there being clarity in their application. Then, it is concluded that the judges of the criminal court do not include in their sentences all the constitutive elements of the objective typicity established by the doctrine; therefore, there is a lack of clarity and uniformity in establishing the objective typicity.